A mobile application to manage and minimise the risk of late effects caused by childhood cancer. - Kock, Ann-Kristin; Kaya, Rafiye; Müller, Christian; Björn Andersen; Langer, Thorsten; Ingenerf, Josef (Studies in health technology and informatics, 2015)
In their first 15 years of life, about 1 800 children are diagnosed with cancer each year in Germany. Their chances of survival, however, have improved significantly over the last 40 years. In Germany alone, over 30 000 survivors of childhood cancer are presently living. Therefore, the late effects caused by the therapy occur ever more frequently as chemotherapy and radiotherapy may leave traces even years later. In order to recognize and treat these late effects in survivors, structured and regular follow-up examinations are necessary from an early stage on. However, the compliance of former patients to participate in the recommended check-ups is not satisfying for multiple reasons. To enhance this compliance, an application for smartphones and tablets has been developed. The Aftercare App supplies a wide range of information regarding the aftercare and supports a reminder functionality to attend medical visits.